Humoral and cellular immune responses to the SARS‐CoV‐2 BNT162b2 vaccine among a cohort of solid organ transplant recipients and healthy controls. Issue 1 (21st December 2021) - Yanis, Ahmad; Haddadin, Zaid; Spieker, Andrew J.; Waqfi, Danya; Rankin, Danielle A.; Talj, Rana; Thomas, Lora; Birdwell, Kelly A.; Ezzell, Lauren; Blair, Marcia; Eason, Joan; Varjabedian, Rebekkah; et al.
Abstract: Background: Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection is associated with increased morbidity and mortality in solid organ transplant (SOT) recipients. Despite exclusion from SARS‐CoV‐2 vaccine clinical trials, these individuals were identified as high‐risk and prioritized for vaccination in public health guidelines. Methods: We prospectively evaluated humoral and cellular immune responses to two doses of the SARS‐CoV‐2 mRNA vaccine, BNT162b2, in 56 SOT recipients and 26 healthy controls (HCs). Blood specimens collected from participants prior to each dose and following the second dose were tested for SARS‐CoV‐2‐specific antibodies, as well as CD4+ and CD8+ T‐cell responses. Results: SOT recipients demonstrated lower mean anti‐SARS‐CoV‐2 antibody levels compared to HCs after each dose, and only 21.6% achieved an antibody response after the second dose within the range of HC responses. Similarly, the percentage of responsive CD4+ and CD8+ T cells in SOT recipients was lower than in HCs. While most HCs showed notable humoral and cellular responses, responses were less concordant in SOT recipients, with some showing evidence of either humoral or cellular response, but not both. Conclusion: Humoral and cellular immune responses to the BNT162b2 vaccine are markedly reduced in SOT recipients as compared to HCs, suggesting that SOT recipients may benefit from more tailored regimens such as higher dose and/or additional vaccinations.